A diagnostic study of some adult genus of wasps in some insect families belong to superfamaly Vespoidea in some provinces of Iraq. - Kazem, Manar Ahmed Abbas (Journal of Kerbala for Agricultural Sciences, 2018)
A diagnostic key was developed to separate the Iraqi species of wasps in the superfamily Vespoidea of Hymenoptera in the insect families Vespidae, Mutillidae, Scoliidae, based on the most important characteristics of the mouth parts (Labrum, Mandiable and Maxillae) . In males and females of some genus. The important parts of the mouth parts used in the diagnosis of these species were photographed. Five species were diagnosed in males and four species in females were registered previously. (Vespa Linnaes 1758 and Polistes Latreille within the Vespidae family), Scoliida Fabricius and Campsomeriella Betrem (Scoliidae family) and Trogaspidia Ashmea (Mutillidae). Keyword: Hymenoptera, mouthparts.